(untitled) (Indian Journal of Public Health Research & Development, 2022)
Back Ground: The major health issues among adolescent girls are early pregnancy, child birth, anemia. Lack of knowledge related to family planning among adolescent girls can adversely affect their and their children lives. Sexual activity in adolescent period is associated with ignorance about sex and sexuality and also predisposed by family traditions of early marriage that can lead to teenage pregnancies leading to illegal abortion, increased IMR and MMR. Adolescents should have knowledge of the health concerns and side effects of contraceptives so that they can make choices to prevent unwanted pregnancies. Aims and Objectives: Assessing the impact of IEC activities on knowledge of family planning among adolescent girls of rural area of Amritsar. Material and Methods: An interventional study was carried out among 13-17 years adolescent girls studying in the Government Senior Secondary Schools at Nagkalan and Sohian Kalan and out of school adolescent girls of the same age group residents of these two villages were also included in the study. IEC activities were done and after three months the effect of intervention was assessed. Among the enlisted 250 eligible adolescent girls, 230 were analyzed and valid conclusions were drawn. Results: out of total 230 respondents, 73 (31.73%) respondents had correct knowledge about legal age of girl at marriage. Out of total 230 respondents, before intervention only 60 (26.0.8%) of the respondents heard about contraceptive methods, after intervention this percentage increased to 68.69%. Conclusion: After intervention more number of adolescent girls had correct knowledge related to family planning